Application and Implementation of ZIS Accounting Based on PSAK 109 at Amil Zakat Institutions (Case Study on Laznas BSM Ummah) - Agus Purnomo; Atika Zahra (Maqrizi: Journal of Economics and Islamic Economics, 2022)
This study is based on the background and also aims to determine the existence of zakat and infaq accounting reports based on PSAK 109. This study uses qualitative methods, the approach used in this study is descriptive. The method used is samples of accounting data from 2020 and 2021. The subject of this study is LAZNAS BSM Umat and the object of this study is the application and implementation of ZIS accounting based on PSAK 109 at amil zakat institution (case study at LAZNAS BSM Umat). From the result of this study, the appropriate zakat and infaq/shodaqoh accounting report based on PSAK 109, therefore can be a communication medium between amil institution and other parties, because ZIS financial report is a form of operation responsibility from the activity of collection and distribution of zakat, infaq, and sadaqah (ZIS). To be a transparent and accountable financial report, therefore there should be an accounting standard to organize this. For the application of ZIS accounting in the presentation of financial reports at LAZNAS BSM Umat has implemented ZIS accounting regulations issued by the Indonesian Accounting Association (IAI) 2010.